The effect of cigarette smoking on inflammatory, immunological and metabolic profiles in ulcerative colitis - Cannon, Aoife (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2016)
Ulcerative Colitis (UC) is an idiopathic form of inflammatory bowel disease characterised by chronic or relapsing inflammation in the colon. The pathogenesis of UC remains largely unknown but it is widely believed to be caused by a complex interplay between genetics, environment, gut microbiota and the immune system. The current paradigm for the pathogenesis of UC is disrupted epithelial barrier function allowing commensal bacterial to cross the epithelial junction where innate immune cells such as macrophages and dendritic cells mount a heightened immune response causing local inflammation and tissue damage, in genetically pre-disposed individuals. The incidence and prevalence of UC is increasing worldwide, in particular in developed countries. Currently, there is no cure for UC and treatment involves control of the disease using steroids, immunosuppressive drugs, biological therapies and possibly surgery to remove all or part of the colon. Interestingly, smoking is well recognised worldwide as having a protective role in UC patients. The incidence and severity of UC is higher in non-smokers than smokers. Despite the clinical evidence supporting the protective effect of smoking in UC, there has been little to no progress made towards understanding the biological mechanism(s) controlling this effect. To date, no studies have examined the effect of cigarette smoke extract (CSE) in ex vivo human colonic UC tissue. Although many studies have examined the effect of nicotine in UC, there has been little work to date examining the effect of other compounds in the cigarette smoke that may be driving this protective effect. This thesis will examine the cellular, molecular and immunological effect of cigarette smoke extract and 2 novel compounds identified from CSE in human ex vivo and mouse in vivo models of colitis
Keywords: Surgery, Ph.D.; PhD Trinity College Dublin, 2016